Karakteristik Psikologis Atlet di Pusat Pendidikan dan Latihan Pelajar (PPLP) - - Dimyati; - Herwin; Tri Ani Hastuti (Faculty of Psychology, Universitas Gadjah Mada, 2013)
The main goal of this study was to describe the psychological characteristics of the athletes of archery, tae kwon do, Pencak Silat, football, athletics, volley ball, and sepaktakraw in the Center for Students Education and Training (CSET). The data were collected from 104 male and female athletes. The study showed that among the groups of athletes of different sports had different psychological characteristics. Footballers had the best motivation, self-confidence, and mental preparation. Athletes of tae kwon do had the best control of anxiety and concentration, but the lowest motivation. Volleyball athletes had the highest team concern, but the lowest concentration, self-confidence, and mental preparation, compared to those from the other sports. The athletes of athletics had the lowest team concern, and the athletes of pencak silat had the lowest control of anxiety compared to athletes from the other sports. Keywords: athletes, CSET, psychological characteristics